Leveraging an existing learning management system for alternative learning - MALIT, MIKAELA (Archīum Ateneo, 2017)
Alternative learning is a practical option for interested learners that have not attended or finished formal basic education. In the Philippines, the Department of Education offers many alternative learning and non-formal programs for every kind of Filipino. While there have been initiatives to integrate information and communication technologies (ICT) in these programs, the use of modern ICT has not been fully realized. This study investigated the effectiveness of introducing an existing learning management system (LMS) as a supplement to the Accreditation and Equivalency Alternative Learning System (ALS) program of the Department of Education. The LMS was intended to aid learning and improve performance by enabling online access to learning materials, delivery of real-time feedback through self-checking interactive quizzes, and self-monitoring of learning progress. A dynamic quiz generation plugin was developed and integrated with Moodle to create interactive quizzes from existing static learning materials. LMS use was monitored in an eight-week implementation in two learning centers where learning gains, LMS usage, usability, access, response, and overall experience were assessed. Based on the analysis of gain scores between the experimental and control groups, the users of the LMS performed better in the posttest. Evaluation of the LMS yielded favorable ratings in usability, and access and response as an online learning environment. Overall, the student and teacher respondents viewed the LMS as a helpful learning tool and encouraged its use in other learning centers. Feedback and suggestions were also gathered from the respondents during evaluation which can be used to improve the LMS.